2020
DOI: 10.1016/j.sjbs.2019.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Chemokines and their association with body mass index among healthy Saudis

Abstract: Obesity is a chronic disorder that is associated with body mass index (BMI) of greater or equal to 30 kg/m2. The prevalence of obesity in the Kingdom of Saudi Arabia (KSA) is increasing at an alarming rate and is expected to reach 41% in men and up to 78% in women by 2022. Since chemokines are associated with involuntary weight loss, the objective of this study was to elucidate their association with BMI among Saudis. A questionnaire was used to collect information about diet, health conditions, and demographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 41 publications
2
27
0
1
Order By: Relevance
“…Some of the recent studies have clearly demonstrated that higher IL-8 levels are associated with obesity. 13 IL-8 levels are also closely correlated with obesity-related parameters like BMI, waist circumference, CRP, IL-6 levels and HDL cholesterol levels. 31 One of the important and most abundant immune cells infiltrating the adipose tissue in obesity are macrophages, 10 and MCP-1 is an important chemoattractant chemokine produced by adipose tissue mediating macrophage recruitment.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…Some of the recent studies have clearly demonstrated that higher IL-8 levels are associated with obesity. 13 IL-8 levels are also closely correlated with obesity-related parameters like BMI, waist circumference, CRP, IL-6 levels and HDL cholesterol levels. 31 One of the important and most abundant immune cells infiltrating the adipose tissue in obesity are macrophages, 10 and MCP-1 is an important chemoattractant chemokine produced by adipose tissue mediating macrophage recruitment.…”
Section: Discussionmentioning
confidence: 92%
“…Some of the recent studies have clearly demonstrated that higher IL-8 levels are associated with obesity. 13 IL-8 levels are also closely correlated with obesity-related parameters like BMI, waist circumference, CRP, IL-6 levels and HDL cholesterol levels. 31 …”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations